Regional Variability in Geotechnical Properties and Slope Stability Mechanisms Across Climatic and Geological Zones of Nepal - Pokhrel, Sarthak (Journal of Engineering Technology and Planning, 2025)
Nepal’s Himalayan terrain, characterized by extreme elevational gradients and heterogeneous lithology, presents region-specific challenges for slope stability and infrastructure resilience. This study evaluates the geotechnical properties of soils from five climatically distinct regions—Kathmandu Valley (subtropical urban basin), Pokhara (humid alluvial valley), Chitwan (forested sub-Himalayan tract), Mustang (arid trans-Himalayan zone), and Terai Plains (tropical lowland)—to establish predictive relationships between soil behavior, environmental factors, and slope failure mechanisms. Laboratory analyses, including triaxial shear testing under unsaturated conditions and advanced permeability profiling were paired with limit equilibrium stability modeling. Results demonstrate that moisture content (R² = 0.87, p < 0.01) and clay mineralogy dominate stability outcomes, with safety factors (FoS) ranging from 0.8 (Terai) to 2.5 (Mustang). A novel regional classification framework is proposed to guide slope management in Nepal’s rapidly developing landscapes.